Values for cooperative games over graphs and games with inadmissible coalitions - Ziv Hellman; Ron Peretz (Bar-Ilan University, Department of Economics, 2015)
We suppose that players in a cooperative game are located within a graph structure, such as a social network or supply route, that limits coalition formation to coalitions along connected subsets within the graph. This in turn leads to a more general study of coalitional games in which there are arbitrary limitations on the collections of coalitions that may be formed. Within this context we define a generalisation of the Shapley value that is studied from an axiomatic perspective. The resulting 'graph value' (and 'S-value' in the general case) is endogenously asymmetric, with the automorphism group of the graph playing a crucial role in determining the relative values of players.
Keywords: C71; D46; D72; 330; Shapley value; network games